A CASE STUDY: BUILDING STUDENTS’ COMPREHENSION IN STUDYING LITERATURE THROUGH RESPONSE ESSAY - Adria Vitalya Gemilang; Ima Widyastuti (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
One of challenges from the students who enrolled on Introduction to Literature subject at Sarjanawiyata Tamansiswa University is how to understand the theories used to analyze a literary work. Until today, there are many researches about literature for English literature students. However, only few managed to combine research on literature and education. This research used the reader response theory by Jauss and Iser, 1978 and Instructional Design Theory by Perkins, 1992. In oder to build the student’s understanding on literature, the students were introduced to response essay writing. They were given several literary works as the materials. After they have finished reading, they write a response essay which analyze the intrinsic elements and reveals their personal experiences related to the literary works. Throughs the students’ response essays, the researchers found that some students fully understood the theory; however, some other students still struggled to convey their understanding due to grammatical lack.Keywords: reader response theory, literature, reading, essay